Pengaruh Model Pembelajaran Flipped Classroom Dengan Pendekatan Etnosains Terhadap Kemampuan Berpikir Kritis Siswa - Oksa Afdarina; Moralita Chatri; Helendra; Irdawati (Jurnal Penelitian Pendidikan IPA, 2024)
The application of the flipped classroom learning model with an ethnoscience approach trains students to learn independently in developing and sharpening critical thinking skills. The aim of the research is to determine the effect of the flipped classroom learning model with an ethnoscience approach on students' critical thinking abilities. This type of research is a quasi-experiment with a non-equivalent control group design. The sample used consisted of two classes, one class was designated as the experimental class and one class as the control class. The purposive sampling method was used to collect samples. The results of hypothesis testing using the t test show that t count is greater than table at a significance level of 0.05, which indicates that the hypothesis H0 is rejected. Thus, the flipped classroom learning model with an ethnoscience approach influences students' critical thinking abilities.